First report of the Anti-Inflation Task Force - Nigeria (Lagos : Federal Ministry of Information, Printing Division, 1975)
This is address to the inaugural meeting of the federal Executive Council held on 13th august, 1975.
Cover title.
Includes bibliographical references.
aia 06/02/2019
Loans
Keywords: Inflation (Finance); Nigeria